Socioeconomic differentials of trends in the prevalence and economic burden of chronic obstructive pulmonary disease in rural southwest China - Le Cai; Xu-Ming Wang; Lan Liu; Yi Zhao; Allison Rabkin Golden (BMC, 2023)
Abstract Background Chronic obstructive pulmonary disease (COPD) is a leading cause of mortality and morbidity, and imposes a substantial financial burden on society. However, few studies have examined the role of individual socioeconomic status (SES) in temporal trends of COPD prevalence and economic cost. This study aimed to uncover the changing prevalence and economic burden of COPD across socioeconomic gradients in rural southwest China. Methods Data were collected from two cross-sectional health interviews and examination surveys administered 10 years apart among individuals aged ≥ 35 years in rural China. A prevalence-based cost-of-illness method was used to estimate the cost of COPD. The individual socioeconomic position (SEP) index was constructed using principal component analysis. Post-bronchodilator spirometry tests were performed for each participant. Results From 2011 to 2021, the prevalence of COPD increased from 8.7% to 12.8% (P < 0.01), while the economic cost of COPD increased 1.9-fold. Unit hospital costs and outpatient costs increased 1.57-fold and 1.47-fold, while unit medication costs fell by 10.6%. Increasing prevalence was also observed when the data were stratified by sex, age, ethnicity, level of education, level of income, and SEP (P < 0.05). Men, ethnic minorities, and those with a lower educational level, lower income, or lower SEP had a higher prevalence of COPD than their counterparts both in 2011 and 2021 (P < 0.05). Unit outpatient costs and medication costs increased with patients' SEP in both survey years (P < 0.05). Conclusions The prevalence and economic costs of COPD increased substantially across all socioeconomic gradients in rural southwest China in the decade from 2011 and 2021. Future COPD prevention and management interventions as well as efforts to improve access to affordable COPD medication and treatment should focus in particular on ethnic minority and low SEP populations.